Determination of the best cooking time and the characteristics of Nile tilapia pepes (an Indonesian traditional fish product) processed by microwave oven - Nasyiruddin, Riya Liuhartana; Al-Ansi, Waleed; Mahdi, Amer Ali; Noman, Anwar; Ilunanwati, Elok; Priyanto, Gatot; Hamzah, Basuni (International Journal of Environment, Agriculture and Biotechnology, 2023)
The present study aimed to examine the best cooking time of Nile tilapia pepes processed by the microwave oven and to observe its chemical characteristics. The research was conducted in two stages. The treatment in the first stage was pepes cooking time which consists of four levels. The observed parameter was pepes sensory using multiple comparison tests. The experimental design to determine the chemical characteristics of pepes in the second stage was Completely Randomized Design with three levels namely raw, steamed, and microwave oven pepes in three replications. The observed parameters were moisture content, protein, amino acids, and free fatty acid levels. The result shows that the best cooking time of pepes with a microwave oven was five minutes. Analysis of variance showed that cooking affected the total selected essential amino acid and 14 kinds of amino acids content that were analyzed, namely aspartic acid, glutamic acid, serine, histidine, threonine, arginine, alanine, tyrosine, methionine, valine, phenylalanine, isoleucine, leucine, and lysine content of pepes but not significantly affected on the moisture content, protein, glycine and free fatty acids content of pepes. The total selected essential amino acid and 14 kinds of amino acids content of raw pepes were significantly different to cooked pepes (microwave oven and steamed pepes), but the total selected essential amino acid and 14 kinds of amino acids content of microwave oven pepes were not significantly different to steamed pepes. The chemical characteristics of microwave oven pepes were 73.04% wb of moisture, 67.95% DB of protein, 28.48% DB of total selected essential amino acids, and 7.22% in oil of free fatty acids content.